Music Autobiographies – Performing Selves - Réka Kovács; Andrada Savin (Acta Universitatis Sapientiae: Philologica)
The article pays tribute to four artists of the music scene, i.e. Bob Dylan, Bruce Springsteen, Patti Smith, and John Luther Adams. It walks in their footsteps through their autobiographies and features the major landmarks in their artistic and creative evolution. Despite the various incongruent traits in their music style, background, or gender, music autobiographies prove to be valuable assets, based on which correlations and contrasts can be elucidated, the road to growing into an artist can be followed, and the creative spirit can be grasped. We hereby conclude that autobiographies can constitute a bridge towards the artistic soul and deepen the understanding of how these musicians project themselves as performers and position themselves in society.